Work stress among teachers: a comparison between primary and secondary school teachers - Kandiah, Kavita; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2018)
The purpose of this study is to identify the level of stress among primary and secondary school teachers and comparing the level of stress based on demographic factors. There are 268 respondents, the samples are teachers from selected primary and secondary schools in a district in Selangor. Survey questionnaire was utilized and the instrument employed is Teacher Stress Inventory and Self Report Teacher Stress Questionnaire. The findings revealed that mean stress level score for teachers in secondary school is higher than primary school with significant difference in the mean stress level for primary (M = 2.13, SD = .558) and secondary school teachers [M = 2.54, SD = .834; t (230) = -4.720, p = .0001]. The study also showed that secondary school teachers perceived more stress in all stress factors which are rapport with parents, rapport with co-worker, work load, time constrain, student attitude, recognition and support and lack of resources than primary school teachers. The result also revealed that there was a significant difference in the mean stress level scores for single and married teachers with mean difference (0.42, p < .05). The finding also indicates that teachers who have teaching experience between 11-15 years experienced more stress and teachers in age between 31-50 years experienced more stress compared to the younger age group (20-30 years) and older age group (51-60 years). It is hoped that the findings will help relevant authorities to design effective stress management programs for the teachers to prevent negative effects of stress.